2015
DOI: 10.1371/journal.pone.0121242
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Promotes Wound Healing in the Skin

Abstract: IntroductionLeptin, a 16 kDa anti-obesity hormone, exhibits various physiological properties. Interestingly, skin wound healing was proven to delay in leptin-deficient ob/ob mice. However, little is known on the mechanisms of this phenomenon. In this study, we attempted to elucidate a role of leptin in wound healing of skin.MethodsImmunohistochemical analysis was performed to confirm the expression of the leptin receptor (Ob-R) in human and mouse skin. Leptin was topically administered to chemical wounds creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
59
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 41 publications
8
59
1
2
Order By: Relevance
“…We considered, but not limited to the following evidence that supports this argument: (1) women relative to men have much lower risk of NMSC32, suggesting that women may have some protections; (2) animal studies showed that withdrawal of ovary dramatically increased susceptibility to NMSC in female mice33, and estrogen receptor-β agonist remarkably decreased UV-induced skin cancer34; and (3) There is evidence that estrogen may promote wound healing and delay or even reverse skin aging through multiple mechanisms (e.g., reduction of inflammation and oxidative damage)3536. Another hormone that is significantly higher in women than in men is adipokine, leptin, which has also been suggested to promote wound repair in the skin (e.g., by accelerating proliferation and enhancing angiogenesis around the wounded)37, and to improve, preserve and restore skin regeneration38. For men and women having an equivalent amount of excess weight, women carry more subcutaneous fat which a major producer of leptin, and this might partly explain the sex-specific difference in the association of BMI with NMSC risk in this study.…”
Section: Discussionmentioning
confidence: 99%
“…We considered, but not limited to the following evidence that supports this argument: (1) women relative to men have much lower risk of NMSC32, suggesting that women may have some protections; (2) animal studies showed that withdrawal of ovary dramatically increased susceptibility to NMSC in female mice33, and estrogen receptor-β agonist remarkably decreased UV-induced skin cancer34; and (3) There is evidence that estrogen may promote wound healing and delay or even reverse skin aging through multiple mechanisms (e.g., reduction of inflammation and oxidative damage)3536. Another hormone that is significantly higher in women than in men is adipokine, leptin, which has also been suggested to promote wound repair in the skin (e.g., by accelerating proliferation and enhancing angiogenesis around the wounded)37, and to improve, preserve and restore skin regeneration38. For men and women having an equivalent amount of excess weight, women carry more subcutaneous fat which a major producer of leptin, and this might partly explain the sex-specific difference in the association of BMI with NMSC risk in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Leptin is mainly secreted by adipocytes and directed to target cells, such as epithelial cells, nervous cells and immune cells expressing its receptor LepR [27,83]. Indeed, leptin is known to stimulate keratinocyte proliferation in vitro and to act as a mitogen during skin repair in vivo [84]. In accordance, LepR is particularly expressed in proliferating basal layer and in neo-epithelial keratinocytes during skin repair [84].…”
Section: Leptinmentioning
confidence: 99%
“…Indeed, leptin is known to stimulate keratinocyte proliferation in vitro and to act as a mitogen during skin repair in vivo [84]. In accordance, LepR is particularly expressed in proliferating basal layer and in neo-epithelial keratinocytes during skin repair [84]. It have been shown activation of the classical leptin pathway via JAK/STAT cascade in human HaCaT cells during wound repair, and induction of keratinocyte-derived proinflammatory cytokines, such as IL-6, IL-8 and TNF-α [85].…”
Section: Leptinmentioning
confidence: 99%
“…Moreover, leptin could be detected immunohistologically in the IPFP of patients in early as well as in end‐stage OA . In connection with trauma, researchers found that leptin has a positive effect on fracture‐healing in mice and wound‐healing of the skin . As far as we know, leptin has not been described in context with articular trauma yet, but the fact that in our subjects leptin expression was higher in the control group could be interpreted as an acute reaction to the trauma in this context and that leptin may support intra‐articular processes, which are a response to the trauma.…”
Section: Discussionmentioning
confidence: 65%